Caractérisation spatiale et mesure des paysages agricoles - Esther Sanz Sanz (Projets de Paysage)
Agriculture is currently considered – through landscape, health and food quality – legitimate as an object of the urban political project to be studied in spatial planning. Agri-urbanism is arising. Nevertheless, from this view, all agricultures are not equivalent. Our hypothesis is that “ecologized” agricultural practices, owing to their production rules, offer additional advantages for complying with social requirements. How can these locally-desired forms of agriculture be characterized and measured so as to support public action ? Our thesis is that the spatial organization of ecologized farming is different from conventional spatial organization. This article makes a brief review of existing methodologies of agricultural landscape spatial characterization by means of indicators, especially those pointing out the differences between the conventional and ecologized model.